Performance of the stereoscopic system of the HEGRA imaging air Čerenkov telescopes: Monte Carlo simulations and observations - Konopelko, Alexander; Hemberger, M.; Aharonian, Felix A.; Daum, A.; Hofmann, Werner; Köhler, C.; Krawczynski, H.; Völk, Heinrich J.; Akhperjanian, A.; Barrio, J.; Bernlöhr, Konrad; Pühlhofer, Gerd; et al. (Astroparticle physics, 1999)
Based on the Monte Carlo simulations we have studied the performance of the HEGRA system of imaging air Čerenkov telescopes (IACTs) in its present configuration of 4 IACTs as well as in its future final configuration of 5 IACTs. Here we present the results on the basic characteristics of the IACT system which are used in the standard data analysis procedure, i.e., the collection areas, the detection rates, the angular resolution, the energy resolution, and the γ/hadron-separation efficiency. By comparing several key Monte Carlo predictions with experimental results it is possible to check the accuracy of the simulations. The Monte Carlo results concerning hadron-nuclear showers are tested with the recorded cosmic ray events and the results concerning photon-induced showers are tested with a large data sample of γ-rays observed from BL Lac object Mkn 501 during its high flaring activity in 1997. Summarizing the simulations and current observations we give the basic recommendations of using the instrument and the major values of its sensitivity.
Gesehen am 26.11.2020